2011
DOI: 10.1007/s12011-011-9108-8
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Serum Selenium Concentration and Neutrophil Function in Peripheral Blood

Abstract: We evaluated the relationships between neutrophil-related functions and serum selenium (Se) concentration in the general population. We examined 800 subjects who had participated in the Iwaki Health Promotion Project in 2005 to determine the relationships between serum Se concentration and neutrophil-related functions such as the production capability of reactive oxygen species (ROS), phagocytic activity, and serum opsonic activity (SOA). In nonstimulated neutrophils, i.e., in neutrophils at their baseline con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This suggests that there may have been a residual effect from the previous supplementation with the micronutrient in these individuals, thus justifying the sustained neutrophil count. Thus we can say that, as noted by other authors, 22,31,32 selenium usage is able to perform a beneficial role on the viability of neutrophils in patients undergoing conditions of increased oxidative stress, such as the patients we studied. It is noteworthy that new studies should be conducted to assess the function of these cells and identify whether this supplementation influences the chemotaxis and digestion of the material phagocytosed by the cell.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This suggests that there may have been a residual effect from the previous supplementation with the micronutrient in these individuals, thus justifying the sustained neutrophil count. Thus we can say that, as noted by other authors, 22,31,32 selenium usage is able to perform a beneficial role on the viability of neutrophils in patients undergoing conditions of increased oxidative stress, such as the patients we studied. It is noteworthy that new studies should be conducted to assess the function of these cells and identify whether this supplementation influences the chemotaxis and digestion of the material phagocytosed by the cell.…”
Section: Discussionsupporting
confidence: 75%
“…21,22,32 The decrease in serum levels of selenium can not only lead to the fall in the number of circulating neutrophils but can also cause changes in lymphocyte functions due to a lower bioavailability of the micronutrient. Through studies …”
Section: Discussionmentioning
confidence: 99%
“…Although, no significant differences were reported in Se and in Zn in men, a trend to increase was evidenced suggesting a better antioxidant profile in people practicing more physical activity. Accordingly, it has been reported that participants with a lower serum Se concentration may be exposed to a greater chronic oxidative stress due to neutrophil reactive oxygen species production [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Opsonization is a humoral immune response involving the complement system that facilitates the capture and uptake of foreign substances by neutrophils and other phagocytes. An increase in SOA causes neutrophil activation and stimulates the secretion of reactive oxygen species (ROS)[ 36 , 37 ], which is associated with physical stress[ 38 - 40 ]. Among ROS, superoxide anions (O 2- ) and hydrogen peroxide (H 2 O 2 ) induce DNA fragmentation in cells, causing inflammation and tissue damage[ 37 ].…”
Section: Assessment Of Physical Stress By Soamentioning
confidence: 99%